2009
DOI: 10.1074/jbc.m109.003269
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Stimulates the Production of Amyloid-β Peptides through Internalization of the EP4 Receptor

Abstract: Amyloid-␤ (A␤) peptides, generated by the proteolysis of ␤-amyloid precursor protein by ␤-and ␥-secretases, play an important role in the pathogenesis of Alzheimer disease. Inflammation is also important. We recently reported that prostaglandin E 2 (PGE 2 ), a strong inducer of inflammation, stimulates the production of A␤ through EP 2 and EP 4 receptors, and here we have examined the molecular mechanism. Activation of EP 2 and EP 4 receptors is coupled to an increase in cellular cAMP levels and activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 58 publications
3
51
0
1
Order By: Relevance
“…Ptger4 encodes a member of the G-protein coupled receptor family, and leads to the phosphorylation of glycogen synthase kinase-3, which can act as a regulatory switch for numerous signaling pathways involved in the neonatal adaptation of the circulatory system, in osteoporosis, as well as in the initiation of skin immune responses (12,13). As Ncf2 encodes a 67-kDa cytosolic subunit of the multi-protein NADPH oxidase complex, its interaction with Ptger4 has been implicated in a number of cardiovascular pathologies, such as atherosclerosis, hypertension and stroke (25).…”
Section: Interactions Among Shr-specific Genes and Candidate Genes Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Ptger4 encodes a member of the G-protein coupled receptor family, and leads to the phosphorylation of glycogen synthase kinase-3, which can act as a regulatory switch for numerous signaling pathways involved in the neonatal adaptation of the circulatory system, in osteoporosis, as well as in the initiation of skin immune responses (12,13). As Ncf2 encodes a 67-kDa cytosolic subunit of the multi-protein NADPH oxidase complex, its interaction with Ptger4 has been implicated in a number of cardiovascular pathologies, such as atherosclerosis, hypertension and stroke (25).…”
Section: Interactions Among Shr-specific Genes and Candidate Genes Rmentioning
confidence: 99%
“…Subsequently, the interactions of these genes were analyzed with Ingenuity Pathway Analysis (IPA). IPA of SHR-specific genes revealed that prostaglandin E receptor 4 (Ptger4) is one of the candidate genes responsible for causing hypertension in SHR (12,13), as well as albumin (Alb) and chymase 1 (Cma1), in the presence of angiotensinogen (Agt) (14)(15)(16). Similar analyses of SHRSPspecific genes revealed that angiotensin II receptor-associated gene (Agtrap) interacts with FBJ osteosarcoma oncogene (Fos), and with angiotensin II receptor type-1B (Agtr1b) (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…pressing APPsw, and the amounts of CTF␣ and CTF␤ were indistinguishable between the APPsw/HSP70 and APPsw/WT mice. We then directly measured ␤-and ␥-secretase activity, using the APP-derived fluorescent substrate of each secretase (Hoshino et al, 2009). As shown in Figure 4C, the activity was indistinguishable between the APPsw/HSP70 and APPsw/WT groups.…”
Section: Effect Of Overexpression Of Hsp70 On A␤ Accumulation and Neumentioning
confidence: 99%
“…This has been populously investigated through studies of its metabolic products, the prostaglandins (PGs), including PGE 2 , PGD 2 [and its dehydration end product 15‐deoxy‐Δ 12,14 ‐PGJ 2 (15d‐PGJ 2 )], PGI 2 , PGF 2α, and TXA 2 (Akarasereenont et al ., 1999). For example, PGE 2 treatment increases the ratio of Aβ 1–42 /Aβ 1–40 production in SH‐SY5Y cells and APP23 transgenic mice (Hoshino et al ., 2007, 2009). In line with these observations, PGE 2 was further verified to stimulate the production of Aβ 1–42 alone in C57BL/6 mice (Echeverria et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%